Kritik Sosial dalam Cerpen PSBB Karya Kedung Darma Romansa: Kajian Sosiologi Sastra - Ika Bella Aprillia Pasaribu; Adinda Soewandi; Wahyu Gaesesita Arlilianda; Wina Lexa Nanda Patricia; Zahratul Umniyyah (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2023)
Social problems are permanent issues that cannot be avoided and easily found among individual’s interactions to others. The state of different interests and necessities triggers the emergence of various clashes in society. The phenomenon is proficiently reflected in literature, as a reflection of real life. Social criticism becomes one of the important instruments in analyzing social issues represented through stories in literary works. In this study, Kedung Darma Romansa’s PSBB becomes a material object for conducting analysis based on social criticism. This qualitative study uses the sociological approach and criticism to reveal social issues in society portrayed through the storyline. Based on the research findings, social criticism revealed are criticism on political issues, customs or culture, economy, household or family, and morals.